Biostratigraphic study of the Paleocene succession at south Wadi Qena, Egypt. (August 2022) - Abudeif, Abdelbaset M.; Tammam, Mohamed A.; Masoud, Ahmed M.; Masoud, Marwa M.
Abstract: This biostratigraphic study of the Paleocene sedimentary sequence at three localities in Qena region, Egypt provides a detailed assessment of the lithological features and planktonic and benthic foraminiferal taxa in order to re-assess the age of the lithologic units, identify possible unconformities, and infer the paleobathymetry and depositional environments. From south to north, these localities are Gebel Serai, Gebel Aras, and Gebel Abu Had where the Dakhla Formation (Danian–Selandian), Tarawan Formation (Selandian–Thanetian), and Esna Formation (Thanetian) are exposed. Biostratigraphic analyses suggest the occurrence of 53 foramineferal species constituting eight planktonic foraminiferal Zones. These are in stratigraphic order: Parvularugoglobigerina eugubina, Parasubbotina pseudobulloides, Praemurica trinidadensis, and Praemurica uncinata biozones (Danian age), Morozovella angulate and Igorina pusilla pusilla biozones (Selandian age), Gloanomalina pseudomenardii Zone (Selandian-Thanetian age), and Igorina laevigata Zone (Thanetian age). In the Middle part of the Dakhla Formation, a bed of marl and shale rich in organic matter approximately ∼1.2 m thick is present, and is rich in both planktonic and benthic foraminiferal species. This unit determines the datum of the last appearance of Pr. uncinata and the boundary between the Danian and Selandian. The Selandian-Thanetian deposits are characterized by planktonic and benthic foraminiferal species of outer neritic environment, whereas the Danian deposits comprise outer neritic planktonic and benthic foraminiferal genera, probably as a result of sea level changes during Danian/Selandian. The contact between the Tarawan and Esna formations coincides with the first appearance datum of Morozovella velascoensis and the last appearance datum of Gl. pseudomenardii . This suggests that the Planktonic 4c is absent in the study area and the Tarawan/Esna contact is paraconformable. The quantitative analysis of the foraminiferal contents in the different formations indicates the high value of planktonic/benthic ratio and low value of agglutinated/calcareous ratio in the middle of the Dakhla Formation and the contact between Tarawan and Esna formations. Thus, by using both lithostratigraphy and biostratigraphy to infer the lateral relationships between facies associations and paleontological changes, and interpreting the depositional environments in terms of relative changes in sea level, this study has added new knowledge about the geologic history of the study area during the Paleocene. Highlights: Biostratigraphically eight planktonic Foraminiferal zones have been recorded. The thickness of a great Paleocene succession in study area about ∼90m. It was formed as outer neritic depth from zone 1a to P5a and contains. Subtropical planktonic foraminiferal assemblages. This boundary is represented by a thin bed of white to gray marl within the.